Periphyton Community Structure on Natural and Artificial Substrates in the Namu Sira-Sira River, Langkat Regency, North Sumatra - Fathia Azzahra; Melfa Aisyah Hutasuhut; Zahratul Idami (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Periphyton is one of the biotic components, living attached to various substrates has an important role in providing primary productivity of waters. The purpose of this study was to determine the identification of species, the structure of the periphyton community in natural and artificial substrates, the water quality of the Namu Sira-sira River in Langkat Regency. The data collection method was carried out using the "Purposive Random Sampling" method at three stations according to community activities in the research area.The results of the study obtained species found in natural substrates were 25 species and artificial substrates were 27 species. The community structure including the diversity index (H ') is included in the medium category with a value of 2.48 on natural substrates and artificial substrates with a value of 2.50. The uniformity index value (E) on natural substrates is 0.89 and artificial substrates are 0.90 categorized as high because the distribution of species in each station is even. Periphyton communities on natural substrates have advantages in terms of abundance and diversity compared to artificial substrates due to the complex interactions between environmental factors, substrate quality, and ecological processes that support their growth